1998
DOI: 10.1074/jbc.273.33.20785
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Stability and Domain Interactions of the Mannitol Permease of Escherichia coli

Abstract: The transport of some carbohydrates from the environment into bacterial cells is mediated by the proteins from the phosphoenolpyruvate-dependent phosphotransferase system (PTS). 1This system couples the translocation of substrates across the cytoplasmic membrane to concomitant phosphorylation, using phosphoenolpyruvate (PEP) as the energy source. Thus, the overall reaction catalyzed by the PTS system is best described as follows.PEP ϩ carbohydrate out 7 pyruvate ϩ P-carbohydrate in REACTION 1The equilibrium of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…4 and Table V). DSC profiles showing two separate unfolding transitions have been observed in the past for proteins containing two separate domains (40,41). The C-terminal domain was found to be fairly thermostable with a T m beyond 80°C, which is astonishing considering the relatively low amount of secondary structure determined by cd spectroscopy (Fig.…”
Section: Calorimetric Titration Of the N-terminal Domain Of Tbpb Withmentioning
confidence: 67%
“…4 and Table V). DSC profiles showing two separate unfolding transitions have been observed in the past for proteins containing two separate domains (40,41). The C-terminal domain was found to be fairly thermostable with a T m beyond 80°C, which is astonishing considering the relatively low amount of secondary structure determined by cd spectroscopy (Fig.…”
Section: Calorimetric Titration Of the N-terminal Domain Of Tbpb Withmentioning
confidence: 67%
“…The existence of such mutations implies a tight coupling between sugar transport through EIIC Glc , the phosphorylation by EIIB Glc , and the conformation around Arg-424 and Cys-421. A conformational coupling between the IIC and IIB domains has been detected previously in the mannitol enzyme IICBA transporter (34).…”
Section: Fig 8 Binding Of Mlc To Membranes Of a Ptsmentioning
confidence: 98%
“…SSCS and SSCS-S124C were purified by Ni-NTA-agarose affinity chromatography as described for 6HEII mtl (14), except that dPEG was used as the detergent. IIChis-CL and IIChis-S124C were purified as described (16).…”
Section: Generation Of Iso Vesicles and Purification Of Sscs Sscs-s1mentioning
confidence: 99%
“…5) Isothermal titration calorimetry experiments indicated that a significant part of the structural changes upon the binding of mannitol to the C domain reside in the B domain. Approximately 50 -60 residues are removed from the bulk water upon binding of mannitol, which was much less when the same measurements were done after removal of the B domain (16). 6).…”
mentioning
confidence: 99%